Socio-demographic correlates of quality of life in spinal cord injured patients - Abiodun L. Azeez; Adebisi I. Hammed (Turkish Journal of Kinesiology, 2019)
Spinal cord injury (SCI) is one of the greatest calamities that can occur in humans' life. It brings about great challenges in the form of coping strategies as well as protocols of rehabilitation and characterized by a high incidence of poor self-rated health. This study investigated socio-demographic correlates of health-related quality of life (HRQoL) among paitents with SCI. Two separate self-rated questionnaires (the socioeconomic status questionnaire (SSQ) and generic SF-36 questionnaire) were administered to each of the participants to evaluate both socioeconomic statuses (SES) and HRQoL respectively. A total of 100 subjects with SCI of mechanical origin, aged 19-59 years participated in this study. Pearson product-moment coefficient of correlation was used to analyze the relationship between HRQoL and socio-demographic parameters (age, gender, marital status, clinical characteristic of morbidity and SES) and however, one-way analysis of variance (ANOVA) was used to analyze the differences in HRQoL across categories of SES. This study indicated that SES and clinical characteristic of morbidity (CCM) were the only variables correlating significantly (p<0.05) with all the domains of HRQoL. In specific terms, the outcome suggested that low SES and complete SCI are associated with poor HRQoL components. However, age, gender, and marital status were all found to associate poorly and insignificantly with most of the HRQoL domains (p>0.05). The present study, therefore, submitted that in this population the most important determinants of HRQoL in SCI patients are SES and CCM. The implication of this finding is viewed in three different perspectives; first poor SES could precipitate the onset of the initial episode of SCI, second poor SES might lead to poor rehabilitation outcome and third long-standing SCI can precipitate low SES.